Espin Actin-Cytoskeletal Proteins Are in Rat Type-I Spiral Ganglion Neurons and Include Splice-Isoforms with a Functional Nuclear Localization Signal - SEKERKOVÁ, GABRIELLA (2008)
The espins are Ca(2+)-resistant actin-bundling proteins that are enriched in hair cell stereocilia and sensory cell microvilli. Here, we report a novel localization of espins to a large proportion of rat type-I spiral ganglion neurons (SGNs) and their projections to the cochlear nucleus (CN). Moreover, we show that a fraction of these espins is in the nucleus of SGNs owing to the presence of splice-isoforms that contain a functional nuclear localization signal (NLS). Espin antibody labeled ~83% of type-I SGNs, and the labeling intensity increased dramatically during early postnatal development. Type-II SGNs and vestibular ganglion neurons were unlabeled. In the CN, espin-positive auditory nerve fibers showed a projection pattern typical of type-I SGNs, with intense labeling in the nerve root region and posteroventral CN (PVCN). The anteroventral CN (AVCN) showed moderate labeling, while the dorsal CN showed weak labeling that was restricted to the deep layer. Espin-positive synaptic terminals were enriched around nerve root neurons and octopus cells in the PVCN and were also found on globular bushy cells and multipolar neurons in the PVCN and AVCN. SGNs expressed multiple espin transcripts and proteins, including splice-isoforms that contain a nonapeptide, which is rich in positively charged amino acids and creates a bipartite NLS. The nonapeptide was necessary to target espin isoforms to the nucleus and was sufficient to target an unrelated protein to the nucleus when joined with the upstream di-arginine-containing octapeptide. The presence of cytoplasmic and nuclear espins in SGNs suggest additional roles for espins in auditory neuroscience.